The use of Netnography in research on the psychology of vulnerable groups: The case of a podcast about alcohol use disorder - Urhan, Bahar; Ata, Fırat; Livberber, Tuba; Çelik, Begüm Birsen Arslan (Edelweiss Applied Science and Technology, 2025)
Alcohol use disorder is a widespread public health problem that affects millions of people worldwide and has social, economic, and cultural repercussions. However, difficulties in reaching vulnerable groups make research on such public health issues challenging. While digital media has the potential to be a powerful tool in the detection, prevention, and treatment of various mental disorders, there are limited studies that specifically address user comments in this context. This study uses a netnographic approach to analyze listeners’ comments on Andrew Huberman’s podcast episode “What Alcohol Does to Your Body, Brain & Health” on the “Huberman Lab” YouTube channel. With nearly 7 million views and more than 11,000 comments, this podcast is significant. By analyzing the 1,200 most engaged comments, the cognitive, emotional, and behavioral responses of the listeners were revealed. This research fills a gap in the literature by providing an understanding of the potential of digital media to contribute to public health issues.